2023
DOI: 10.1101/2023.04.20.537685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

replicAnt: A pipeline for generating annotated images of animals in complex environments using Unreal Engine

Abstract: Deep learning-based computer vision methods are transforming animal behavioural research. Transfer learning has enabled work in non-model species, but still requires hand-annotation of example footage, and is only performant in well-defined conditions. To overcome these limitations, we created replicAnt, a configurable pipeline implemented in Unreal Engine 5 and Python, designed to generate large and variable training datasets on consumer-grade hardware instead. replicAnt places 3D animal models into complex, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…This effect was particularly evident for recordings from cluttered environments (Fig. 10, B,C,H,I), and mirrors similar results in earlier work, which suggested that synthetic data can help to embed a subject-specific understanding into the networks [45]. In the context of body mass inference, a key strength of synthetic data is that it can be generated such that size-related differences in cropped image occupancy or compression artefacts are entirely avoided, so preventing networks from learning to infer size from these artefactual features, which would impede generalisation.…”
Section: Augmenting Real Annotated Data With Synthetic Samples Improv...supporting
confidence: 88%
See 4 more Smart Citations
“…This effect was particularly evident for recordings from cluttered environments (Fig. 10, B,C,H,I), and mirrors similar results in earlier work, which suggested that synthetic data can help to embed a subject-specific understanding into the networks [45]. In the context of body mass inference, a key strength of synthetic data is that it can be generated such that size-related differences in cropped image occupancy or compression artefacts are entirely avoided, so preventing networks from learning to infer size from these artefactual features, which would impede generalisation.…”
Section: Augmenting Real Annotated Data With Synthetic Samples Improv...supporting
confidence: 88%
“…To implement augmentation on a large scale, we produced thousands of computer-generate images that possesses far greater variability in appearance than the original training data. Synthetic datasets were generated with replicAnt , a computational data generation pipeline implemented in Unreal Engine 5 and Python [45]. replicAnt takes textured and rigged 3D animal models as an input, and places simulated populations of these models into complex, procedurally generated environments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations